Watering down ethnography - Jowsey, Tanisha (BMJ quality & safety, 2016)
Where ethnography originated in exploration of the exotic and unknown 'other', it can now be used in local spaces, and indeed, in auto-ethnographic modes to understand the self as subject. 5 But what is the difference between writing an autobiography or a descriptive piece and something ethnographic? 6 Lamba et al write that two of the three authors (ARL and KL) had special training in quality and safety but in this article no mention is made of the ethnographic training, or the ethnographic methods or any ethnographic theoretical stance.